The Effect of Environmental Social Governance, Good Corporate Governance, and Capital Structure on the Firm Value of Basic Material Companies in Indonesia (2019-2023) - Agustin, Fasya Nur Aini; Paramita, Veronika Santi (Sinergi International Journal of Accounting and Taxation, 2025)
This study seeks to examine firm value in the basic material sector companies from 2019 to 2023. During the 2019-2023 period, the value of the basic material sector companies tended to decrease. The objective of this research is to examine whether the firm value of basic material sector companies listed on the IDX for the 2019-2023 period is influenced or not by Environmental Social Governance, Managerial Ownership, Institutional Ownership, Audit Committee, and Debt to Equity Ratio. This study employs a quantitative approach featuring descriptive causality analysis, utilizing panel data obtained from secondary sources. The researcher determined the basic materials sector as the population and eight companies as the sample. The purposive sampling method was used to conduct this sampling. Panel data regression is applied by the researcher to analyze the data. The findings indicate that partially that ESG, along with managerial and institutional ownership positively affects the value of the firm. However, firm value does not seem to be impacted by the audit committee and DER. Simultaneously, firm value is affected by ESG, managerial ownership, institutional ownership, audit committee, and DER.